Determinants of Demand for Physical Activity among Students in Krakow - Kościółek Szczepan (Sciendo, 2017)
The low level of physical activity amongst Poles is not only a social problem, but also a big challenge for commercial organizations. The aim of the thesis was to determine indicating factors influencing the maximum price that students are prone to pay for physical activity. The research was based on the opinions of 398 respondents (students from Krakow's academies). A Chi-square test of independence was used to compare the distribution of the observed variables with their theoretical distribution.